State Finance Commissions and rural local bodies: devolution of resources - Geetha Rani, P. (1999)
The 73rd and 74th Constitutional Amendment Acts, 1992 have added a new dimension of fiscal federalism and decentralised public finance in the Indian federal system. The structure of intergovernmental fiscal relations and transfers necessarily will have to undergo significant changes. Their provisions relating to the creation of State Finance Commissions (SFCs) to rationalise fiscal relations at the sub-state level and make periodic fiscal corrections assume significance in this context. This paper seeks to critically review the recommendations of five SFCs, viz. Karnataka, Kerala, Punjab, Rajasthan and West Bengal, on fiscal devolution with reference to rural local bodies - the Panchayati Raj Institutions (PRIs). - Reproduced
Keywords: Public finance - India; Public finance